Pembuatan Membran Dari Ampas Tebu dan Aplikasinya Untuk Menyaring Air Tanah dan Air Gambut - I Nyoman Candra; Sugiono; Hermansyah Amir (ALOTROP, 2022)
The production and use of a membrane filter made from bagasse (Saccharum officinarum) to filter ground water and peat water had been conducted. The purpose of this research are to evaluate the yield of membrane filter produced from bagasse, assess its ability to filter ground water and peat water as well as to measure the physical and chemical properties covering pH, turbidity and iron concentration, of those waters after filtered out with the membrane filter. Bagasse was used as a raw material for producing membrane filter through pulping process, followed by vulcanized fiber method using ZnCl2. From 100 g of bagasse, 38.7% membrane filter was produced. The membrane filter could increase ground water and peat water quality by increasing ground water and peat water pH from 6.7 to 7.2 and from 6.1 to 7.4 respectively. It also reduced ground and peat water turbidity from 48.33 to 1.67 NTU (96%) and from 65 to 2.67 NTU (96%) respectively. Iron concentration declined from 4.67 to 0.056 mg/L (for ground water) and from 3.645 to 0.121 mg/L (for peat water) respectively. Membrane filter produced from bagasse could improve ground and peat water quality after filtered out, whose physical and chemical properties met the quality standard of water according to Health Ministry Regulation of Republic of Indonesia No.492/Menkes/Per/IV/2010.